Politeness Principles on Kalembo Ade Phrase and Correlation with Language Education: A Pragmatic Analysis - Sahrain, Muhammad; Diha, Hamjah; Ria Hendriani (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2025)
This study aims to describe the meaning of the Kalembo Ade phrase from the perspective of the Politeness Principle and correaltion with language education.This study was designed as a descriptive qualitative study. Within this method, there is potential for researchers to engage with meaning carried out in a speech event from various events. Therefore, this study employed a pragmatic approach to come with relevant findings. Data were collected from various speech events between children and parents, adults, teenagers, and teenagers and parents. Data, which were in the forms of utterances, were taken in some places and situations, including in a public bus, garden, farm, houses, and neighborhood. The result shows that there are four politeness princples that contained on Kalembo Ade phrase, such as Maxim of Generosity, Maxim of Sympathy, Maxim of Generosity, and Maxim of Appreciation. Based on the results of the analysis, a correlation exists between the expression and education, specifically encompassing the aspects of Cross-Cultural Pragmatics and Sociolinguistics Learning and Curriculum Development for Local Language and Culture.